Whistle-stop tour of statistics - Everitt, Brian S. (Boca Raton : CRC Press, 2012)
"Preface according to my Penguin English dictionary, whistle-stop, used before a noun means 'consisting of brief stops in several places' and this whistle-stop tour of statistics does just that, with the ten 'stops' being ten major areas of statistics. In a Whistle-Stop Tour of Statistics quintessential accounts of the topics which are the subject of each part are given with the summaries at the end of each part collecting together the most important formulae, etc. The book is intended as a quick source of reference and as an aide-memoir for students taking A-level, undergraduate or postgraduate statistics courses. The numerous examples included in the 'tour' may also be helpful to instructors on such courses in providing their students with small data sets to work with. The book was partially suggested by the two excellent 'companions' by A.C. Fischer-Cripps: Fischer-Cripps, A.C. (2003). The Physics Companion, Taylor & Francis, New York. Fischer-Cripps, A.C. (2005). The Mathematics Companion, Taylor & Francis, New York. B.S. Everitt, Dulwich"--
"A Chapman & Hall book."
Includes bibliographical references and index.
Keywords: Mathematical statistics; MATHEMATICS / Probability & Statistics / General; MATHEMATICS / Probability & Statistics / Bayesian Analysis